PEMETAAN POSISI DAN ORIENTASI KURSI RODA CERDAS BERBASIS PRINSIP DEAD RECKONING - Setiawan, Iwan; Akrom, Isnan Fauzan; Darjat, Darjat (Departemen Teknik Elektro, Universitas Diponegoro, 2009)
Smart wheelchairs is a kind of assistive technology implementation from mobile robot field. The main purpose of the system is enhance disable people mobility and guaranteeing safety aspect while wheelchair navigate around domestic environment. As a kind of semi autonomous smart navigation system, the smart wheelchair must be accommodate share control between automatic controller and the user (via joystic). The ultimate goal of this research is to know exactly the position and orientation of smart wheelchair using dead reckoning principle. To fulfill the goal, the smart wheelchair is equipt by quadrature rotary encoder for each wheels.From the experiments that we drawn, we have get some result: Position and orientation error will be larger for long duration of operation of wheelchairs. Fundamentally, these kinds of error result from systematic and non systematic error source. Keywords: encoder, dead reckoning, state chart, komunikasi serial, smart wheelchair